The Effect of Orienteering Applications on Students' Spatial Thinking Skills in Social Studies: The Case of Turkey - YİĞİT, Turan; KARATEKİN, Kadir (Institute for Advanced Studies, 2021)
Spatial thinking skills are competencies individuals will need in their lives in order to know and understand the world and to perceive the space correctly. In order for individuals to have these competencies, effective traning in the development of spatial thinking skills should occur. Spatial thinking skills can be acquired through student-centered, active learning and orienteering activities, all of which can be applied in lessons as a type of game instead of through traditional teaching methods and techniques. In this study, it is aimed to investigate the effect of spatial thinking skills on the orienteering practices of students' in primary school Grade 4 Social Studies course. The study group consists of a total of 104 students: 51 students are in the experimental group and 53 students are in the control group. All participants are in Grade 4 at a primary school in Merkez district of Kastamonu province in Turkey during the 2019-2020 academic year. Lessons were taught with activities based on orienteering practices in the experimental group, and curriculum-based instruction was conducted in the control group. In the research, one of the quantitative research methods was used as a quasi-experimental model with a pretest-posttest control group. The Spatial Thinking Skill Test (STSS) developed by the researcher was used as the data collection tool. As a result of the research, it was concluded that orienteering practices are effective in developing students' spatial thinking skills. Orienteering is recommended to be used as a teaching technique in Social Studies lessons because it is an entertaining activity that enables learning by doing, the development of multi-faceted thinking, and the transference of spatial thinking skills to daily life.
Keywords: 4. Education; 3. Good health